Regional sales performance evaluation and its challenges in a multinational enterprise - Väisänen, Heta Tuulia (My University, 2013)
Performance evaluation has proven its significant role as part of beneficial organizational development and success of the management practice. However, the previous literature covers typically only the national level solutions, which are not always applicable to different regional contexts. If countries or even larger areas are considered as homogenous units, regional disparities, strengths, weaknesses and different competitive situations are ignored. Realistic and reliable information about regional differences in performance evaluation are argued to enable transparency in the decision-making, more realistic target-setting, better allocation of resources and more comprehensive steering and monitoring for the related organizations. The purpose of this study is to provide descriptive information about the process of regional performance evaluation and its challenges during the different phases by conducting a case study with interviews and desk study of 18 country examples within a multinational white goods producer. The related research problem is to identify what are the characteristics and challenges of regional performance measurement process by economic indicators in multinational enterprises. The study is conducted in the context of international white-good supplier (company A) by running a case study about their approaches to develop a concept for regional sales performance evaluation with economic indicators during 1990-2012 in 18 different country subsidiaries. As a result, this research forms a procedural model for regional performance evaluation covering the main challenges and pain points that appeared in the country examples; reflecting them with previous research and theoretical models. The research method of the study is a qualitative case study conducted with a content analysis covering archived materials and documents about the country approaches and expert interviews for company A employees with special knowledge related to the subject. In total four persons were interviewed in order to be able to understand archival materials, the context in which the performance evaluation was run as well as the insights of the procedure and challenges of the implication. The interviews were conducted as open-ended theme interviews. The desk study data covered archival materials, calculations and documentations about the performance evaluation run in each country. Results of the analysis constituted a circular process model with six phases discussing the methods applied in the country cases and challenges that appeared. The six phases were selection of scope and indicators; data collection; estimations and calculations; rankings and classifications; data interpretation; and finally target fulfilment evaluation and setting the targets for the next period. The main challenges identified were availability of reliable information, the nature of the white good market and client structure, regional heterogeneity and the contextual factors as well as the interpretation of the evaluation results. The main conclusion is that the process of regional performance evaluation in the multinational companies contains many complex aspects and many of these challenges are not addressed in the theoretical framework for performance evaluation. It is discussed, how useful it is to run ad hoc analyses about regional performance, considering the amount of efforts the information acquisition and thorough evaluation require. It is stated that valuable insights could be achieved if the regional performance evaluation process would be developed to be a continuous and strategy-aligned system which considers the characteristics and challenges of regional performance evaluation and combines quantitative, qualitative and procedural measures bringing together different stakeholders.
Keywords: Performance evaluation; Sales Force Management; Regional analysis; fi=Johtaminen ja organisaatiot|en=Management and Organization|; fi=Kasvuyrityksen johtamisen maisteriohjelma|